Redacción técnica y su aporte en la elaboración de documentos oficiales en la secretaría de la FAC.C.J.S.E de la Universidad Técnica De Babahoyo - Sobenis Flor, Rosa Angélica (2019)
In this case study entitled "TECHNICAL DRAFTING AND ITS CONTRIBUTION IN THE ELABORATION OF OFFICIAL DOCUMENTS IN THE SECRETARIATS OF THE FACULTY OF SCIENCES, SOCIAL AND EDUCATION OF THE TECHNICAL UNIVERSITY OF BABAHOYO", shows that technical writing is a necessary requirement , fundamental and indispensable when writing an official document such as letters, offices, reports, minutes, requests, memorandum, etc., whether in an entity, public or private, because this helps us to structure a writing in a clear, simple way and correct. The development of this case study is made up of its theoretical support, such as the independent variable Technical Writing and the dependent variable Preparation of Official Documents that tries to explain what technical writing is, its importance, methods, techniques, characteristics and how they contribute in the elaboration of official documents. To know with certainty, how important is the technical writing in the preparation of official documents, a survey was conducted of all the secretaries of the FACULTY OF SOCIAL SCIENCES, SOCIAL LEGAL AND EDUCATION of the TECHNICAL UNIVERSITY OF BABAHOYO and according to the data obtained, it will be possible to know if the secretaries of this faculty need to acquire and reinforce their knowledge about the writing of official documents with the application of technical standards